Morphological, physiological, and transcriptomic analysis of Taxodium mucronatum under different salinity stresses - Gao, Yunpeng; Wang, Hongling; Shi, Shizheng; Huang, Ruifang; Liang, Liwen; Zhang, Jue; Jiang, Kaipeng; Huang, Tao; Li, Shuxian; Lei, Cong; Dai, Yawen; Sui, Dezong (Frontiers in Plant Science, 2026)
IntroductionSoil salinity is a pressing global issue that undermines agricultural productivity, driving the search for salt-tolerant species and their adaptive strategies. Taxodium mucronatum, a tenacious afforestation tree species, is known for its notable resistance to abiotic stresses. However, its molecular response to salt stress is still unknown.MethodsIn this study, we explored the physiological and transcriptomic adaptations of T. mucronatum seedlings when exposed to different NaCl concentrations (0 ‰, CK; 3 ‰, LS; 5 ‰, MS; 7 ‰, HS).Results and discussionThrough morphological and biochemical analyses, we identified a salinity threshold of 5 ‰. Beyond this threshold, severe leaf senescence and plant death were observed. In physiological profiling, the malondialdehyde (MDA) and relative conductivity (REL) showed dose-dependent increases. Meanwhile, osmoprotectants like proline (PRO), soluble sugar (SS), and soluble protein (SP), as well as antioxidant enzyme activities including peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD), were elevated. This indicates dynamic responses to osmotic and oxidative stress. Transcriptome sequencing revealed 3,858 differentially expressed genes (DEGs). GO and KEGG analyses showed that the commonly up-regulated genes were enriched in ‘oxidoreductase activity’ (GO:0016491) and ‘phenylpropanoid biosynthesis’ (ko00940), whereas down-regulated genes were enriched in ‘cell-wall organization’ (GO:0071554). Among the 421 differentially expressed transcription factors, ERF, WRKY and NAC families constituted 62% of the total, indicating their central role in the salt response. With Weighted Gene Co-expression Network Analysis (WGCNA), we first linked gene modules to physiological traits and found that the MEbrown (r = 0.67–0.99) positively and MEblue (r = –0.69 to –0.98) negatively drives osmoprotectant/antioxidant activation. From these modules, 12 hub genes —especially TCTP, ECI3, PGL3, OsI_15387, APF2, CYP73A4— were identified that coordinate stress adaptation via cell wall remodeling, energy metabolism, and redox homeostasis. This study offers the first in-depth analysis of salt tolerance mechanisms in T. mucronatum, revealing genotype-specific strategies to cope with ionic and osmotic stress. The findings enhance our molecular understanding of stress resilience in woody perennials and highlight the potential for ecological restoration of T. mucronatum in saline-alkali ecosystems.